Glow-Worms, Railroad-Worms (Insecta: Coleoptera: Phengodidae) - Marc Branham (EDIS)
The family Phengodidae are uncommonly encountered beetles that have bioluminescent females that appear to be larvaiform (or larger versions of the immature stage.) These adult females are able to produce light from paired photic organs located on each body segment (one glowing spot on each side) and sometimes also from luminous bands that extend across the dorsal surface of the body between each body segment. Females appear to be more commonly encountered than larvae. Because these glowing spots along the females body resemble the windows of train cars internally illuminated in the night, they are often referred to as "railroad-worms." Males of these species are not larviform, but instead resemble other beetles, though their first pair of wings (elytra) are less then half as long as their hind wings and the males of most species have very elaborate, feather-like antennae. These fancy antennae are used to detect and follow pheromones produced by the female. This document is EENY-332 , one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: December 2004. Revised: February 2005.